The Impact of Islamic Education Teachers’ Competencies on Students’ Learning Outcomes: Evidence from SMA Negeri 4 Kota Bima - Akhyar; Luthfiyah; Syarifuddin (Journal of Educational Studies, 2026)
This study aims to empirically investigate the influence of pedagogical, professional, personal, social, and religious competencies of Islamic Education teachers on students’ learning outcomes at SMA Negeri 4 Kota Bima. The study is based on the assumption that teachers play a central role in determining the effectiveness and success of the learning process, particularly in Islamic Education, which emphasizes not only students’ cognitive achievement but also the development of moral values, attitudes, and practical skills. This research employed a quantitative approach with a correlational research design to examine the relationship between teachers’ competencies and students’ academic performance. The population of the study consisted of all students at SMA Negeri 4 Kota Bima, while the sample was selected using purposive sampling techniques. Data were collected through questionnaires, observations, and documentation and were analyzed using multiple linear regression analysis. The findings revealed that pedagogical, professional, personal, social, and religious competencies simultaneously have a significant influence on students’ learning outcomes. Furthermore, each competency individually contributes positively to improving students’ academic achievement, with pedagogical and religious competencies showing the most dominant influence compared to the other variables. These findings indicate that teachers’ ability to effectively manage classroom learning and to demonstrate exemplary religious values in daily practice are essential factors in enhancing students’ learning success. Therefore, the comprehensive development of Islamic Education teachers’ competencies is highly necessary to improve the quality of students’ learning outcomes. This study is expected to provide valuable insights for schools and educational policymakers in designing strategic programs aimed at strengthening teacher professionalism and promoting effective, meaningful, and nationally oriented educational practices.